Lb3.259 E-STI testing and results service: a single blind randomised controlled trial. (8th July 2017) - Wilson, Emma; Free, Caroline; Morris, Tim P; Syred, Jonathan; Menon-Johansson, Anatole S; Palmer, Melissa J; Barnard, Sharmani; Rezel, Emma; Baraitser, Paula
Abstract : Introduction: STI self-sampling accessed via the internet (e-STI testing) is recommended to expand access to services. There is limited evidence on its effectiveness. This is the first RCT to evaluate an e-STI testing service for chlamydia, gonorrhoea, HIV and syphilis. Methods: Single-blind RCT with allocation concealment. Eligibility: aged 16–30, resident in 2 boroughs of London, having at least one sexual partner in the last 12 months, willing to take an STI test. Participants were randomly allocated to (1) an e-STI testing service or (2) to a website with signposting to local sexual health clinics. Primary outcomes were: 1) diagnosis of any STI 2) completion of any STI test All analyses were intention-to-treat. We used multivariate imputation using chained equations (MICE) for the primary analyses. We explored heterogeneity by age, gender, ethnicity, deprivation, number of sexual partners in the last 12 months, and sexuality. Results: 2072 participants were randomised. The response rate was 84%. At 6 weeks, 50.0% of the intervention group completed an STI test compared to 26.6% in the control group (RR 1.87, 95% confidence interval 1.63 to 2.15, p<0.0001). 2.8% of the intervention v 1.4% in the control were diagnosed with an STI (RR 2.10, 95% confidence interval 0.94 to 4.70, p=0.079). The effect on cases treated was 1.1% in the intervention v 0.7% in the control (RR 1.72, 95% confidence interval 0.71 to 4.16, p=0.231). No heterogeneity was observed in the pre-specified sub group analyses. Time-to-test was lower in the intervention arm compared to the control arm (28.8 days vs 36.5 days; p<0.0001). No differences were observed for time-to- treatment (83.2 days vs 83.5 days; p=0.51). Data cleaning and data collection were still underway late 2016. Conclusion: e-STI testing increased testing uptake and may yield a small increase in STI diagnoses. Service innovations may be needed so that gains in testing and diagnoses translate into similar gains in cases treated. e-STI testing could be a valuable option in high prevalence contexts where expanding access is priority.